Exploring the role of technology in human trafficking in Pakistan: A qualitative study of lived experiences of victims - Zeeshan Khan; Mohammad Rahim Kamaluddin; Jamiah Manap; Surendran Rajaratnam; Masnizah Mohd; Ibrahim Maclean Chong; Farhan Navid Yousaf; Ratna Yunita Setiyani Subardjo (PLoS ONE, 2025)
With the ongoing digital transformation, the internet, mobile, social media and other computer technologies are being increasingly used in the targeting, recruitment, transportation and exploitation of human trafficking victims. The current study is the first of its kind which uses a qualitative method to comprehensively investigate the role of technology in the lived experiences of human trafficking victims in Pakistan. This qualitative study was carried out with a phenomenological approach in two provinces of Pakistan. Data was collected using in-depth interviews with 13 victims who were selected using purposive and snowball sampling methods. The data was then analyzed using Braun and Clarke’s thematic analysis approach. The data analysis results were divided into four main themes and ten sub-themes. The main themes are: Recruitment approaches, transportation process, exploitation process, and mental health consequences. The analysis show that traffickers extensively use technology across all phases of human trafficking. This study aims to support a range of relevant institutional stakeholders, including law enforcement agencies, legislative bodies, policymakers, civil society and SDG (2030) goals, in Pakistan and globally, in their efforts to address and enhance the learning and awareness level regarding related technologies in order to improve investigation in combating technological based human trafficking.